The transformation of Central Asia : states and societies from Soviet rule to independence - Jones Luong, Pauline (Cornell University Press, 2003)
With the fall of the Soviet Union in 1991, former Communist Party leaders in Central Asia were faced with the daunting task of building states where they previously had not existed: Kazakhstan, Kyrgyzstan, Tajikistan, Turkmenistan, and Uzbekistan. Their task was complicated by the institutional and ideological legacy of the Soviet system as well as by a more actively engaged international community. These nascent states inherited a set of institutions that included bloated bureaucracies, centralized economic planning, and patronage networks. Some of these institutions survived, others have mutated, and new institutions have been created. Experts on Central Asia here examine the emerging relationship between state actors and social forces in the region. Through the prism of local institutions, the authors reassess both our understanding of Central Asia and of the state-building process more broadly. They scrutinize a wide array of institutional actors, ranging from regional governments and neighborhood committees to transnational and non-governmental organizations. With original empirical research and theoretical insight, the volume's contributors illuminate an obscure but resource-rich and strategically significant region.